Framing Naturalism Philosophy's Axiological Synergy in Management-Christian Religious Education - Sinta, Grasela; Lestary, Devi; Tanzania, Tirza; Napat, Saul; Mariani, Evi; Munte, Alfonso (Indonesian Journal Publisher, 2023)
Background of the writing would like to present a variety of arguments about the philosophy of naturalism that is often inclined to intelligence, care thinking about nature, resistance tools for land and forest plowing, capitalism in the economic sector, culture / culture and issues about employment. Based on this background, researchers try to answer by taking the other side of the examination, namely through the study of humanities disciplines, specifically management, education, education management, Christian education management and Christian religious education. Based on a qualitative research, the researchers searched for data through secondary sources, namely through previous research journals and sources from books related to the philosophy of naturalism. Results showed that the philosophy of naturalism becomes relevant or not, basically the philosophy of naturalism experienced a shift in meaning with the addition of spirituality in the 19th and 20th centuries as one of the ways to take the philosophy of naturalism